A black-figure amphora from the Gołuchów collection of the national museum in Poznań - Głuszek, Inga (Acta Archaeologica Lodziensia, 2022)
The collection of the National Museum in Poznań includes a black figured amphora, which was once a part of the collection of Countess Izabela Działyńska née Czartoryska located in the castle in Gołuchów. The vessel shows the farewell scene of the warrior surrounded by family members on both sides. The vessel, mentioned by John D. Beazley in his book Greek Vases in Poland and described in the Polish series of Corpus Vasorum Antiquorum, is here re-analysed in order to clarify the chronology, and to define the workshop of the painter who decorated the vessel.